Factors Influencing Pregnancy and Postpartum Weight Management in Women of African and Caribbean Ancestry Living in High Income Countries: Systematic Review and Evidence Synthesis Using a Behavioral Change Theoretical Model - Moore, Amanda P.; Flynn, Angela C.; Adegboye, Amanda Rodrigues Amorim; Goff, Louise M.; Rivas, Carol A. (Frontiers in Public Health, 2021)
Background: Women of black African heritage living in high income countries are at risk of obesity and weight-related complications in pregnancy. This review aimed to synthesise evidence concerning attitudes to weight management-related health behaviours in pregnancy and postpartum, in women of black African ancestry, living in high-income countries. Methods: A systematic review of the literature and thematic evidence synthesis using the Capability-Opportunity-Motivation behavioural change theoretical model (COM-B). Databases searched included MEDLINE, EMBASE, Web of Science and Scopus. The CASP tool was used to assess quality. Results: Twenty-four papers met the selection criteria, most of which were from the US. Motivational factors were most commonly described as influencers on behaviour. Normative beliefs about ‘eating for two’, weight gain being good for the baby, the baby itself driving food choice, as well as safety concerns about exercising in pregnancy, were evident and were perpetuated by significant others. These and other social norms, including a cultural acceptance of larger body shapes and daily fast food, created a challenge for healthy behaviour change. Women also had low confidence in their ability to lose weight in the postpartum period. Behaviour change techniques, such as provision of social support, use of credible sources and demonstration may be useful to support change. Conclusions: These women face a range of barriers to engagement in weight-related health behaviours at this life-stage. Using a theoretical behaviour change framework can help identify contextual factors that may limit or support behaviour change.